Systematic analysis of lysine 2-hydroxyisobutyrylation posttranslational modification in wheat leaves. - Bo Feng (Public Library of Science (PLoS), 2021)
Lysine 2-hydroxyisobutyrylation (Khib) is a recently discovered post-translational modification (PTM) showing diverse biological functions and effects in living organisms. However, the study of Khib in plant species is still relatively limited. Wheat (Triticum aestivum L.) is a global important cereal plant. In this study, the systematic Khib analysis was performed in wheat leave tissues. A total of 3004 Khib sites in 1104 proteins were repeatedly identified. Structure characterization of these Khib peptides revealed 12 conserved sequence motifs. Function classification and enrichment analysis indicated these Khib proteins showed a wide function and pathway distribution, of which ribosome activity, protein biosynthesis and photosynthesis were the preferred biological processes. Subcellular location predication indicated chloroplast was the dominant subcellular compartment where Khib was distributed. There may be some crosstalks among Khib, lysine acetylation and lysine succinylation modification because some proteins and sites were modified by all these three acylations. The present study demonstrated the critical role of Khib in wheat biological and physiology, which has expanded the scope of Khib in plant species. Our study is an available resource and reference of Khib function demonstration and structure characterization in cereal plant, as well as in plant kingdom.